Applying Phase Equilibria Modelling to Metamorphic and Geological Processes: Recent Developments and Future Potential - Yakymchuk, Chris (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2017)
Phase equilibria modelling has played a key role in enhancing our understanding of metamorphic processes. An important breakthrough in the last three decades has been the ability to construct phase diagrams by integrating internally consistent datasets of the thermodynamic properties of minerals, fluids and melts with activity–composition models for mixed phases that calculate end-member activities from end-member proportions. A major advance in applying phase equilibria modelling to natural rocks is using isochemical phase diagrams to explore the phase assemblages and reaction sequences applicable for a particular sample. The chemical systems used for modelling phase equilibria are continually evolving to provide closer approximations to the natural compositions of rocks and allow wider varieties of compositions to be modelled. Phase diagrams are now routinely applied to metasedimentary rocks, metabasites and intermediate to felsic intrusive rocks and more recently to ultramafic rocks and meteorites.While the principal application of these phase diagrams is quantifying the pressure and temperature evolution of metamorphic rocks, workers are now applying them to other fields across the geosciences. For example, phase equilibria modelling of hydrothermal alteration and the metamorphism of hydrothermally altered rocks can be used to determine ‘alteration vectors' to hydrothermal mineral deposits. Combining the results of phase equilibria of rock-forming minerals with solubility equations of accessory minerals has provided new insights into the geological significance of U–Pb ages of accessory minerals commonly used in geochronology (e.g. zircon and monazite). Rheological models based on the results of phase equilibria modelling can be used to evaluate how the strength of the crust and mantle can change through metamorphic and metasomatic processes, which has implications for a range orogenic processes, including the localization of earthquakes. Finally, phase equilibria modelling of fluid generation and consumption during metamorphism can be used to explore links between metamorphism and global geochemical cycles of carbon and sulphur, which may provide new insights into the secular change of the lithosphere, hydrosphere and atmosphere.